2015
DOI: 10.1007/s10681-015-1507-z
|View full text |Cite
|
Sign up to set email alerts
|

Pollen variation as a response to hybridisation in Populus L. section Aigeiros Duby

Abstract: Interspecific hybrids often produce extensive gametic variation due to poor chromosome pairing and unbalanced chromosome segregation. To elucidate the influence of interspecific hybridisation on pollen variation in Populus L., we compared pollen size among three P. deltoides Marsh. clones, two P. nigra L. clones, and three P. deltoides 9 P. nigra hybrids and investigated the cytological mechanism of pollen variation by observing meiotic chromosome behaviour and microtubules. The frequency of shrunken and unsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Perpendicular spindle (Fig. 4F) in this study presented as a cross and chromosomes were compline which was distinct from other studies (Zhang and Kang, 2010;Tian et al, 2015). Besides, we observed other various abnormalities such as unseparated cytoplasm (Fig.…”
Section: Damage Of Floral Budscontrasting
confidence: 52%
See 1 more Smart Citation
“…Perpendicular spindle (Fig. 4F) in this study presented as a cross and chromosomes were compline which was distinct from other studies (Zhang and Kang, 2010;Tian et al, 2015). Besides, we observed other various abnormalities such as unseparated cytoplasm (Fig.…”
Section: Damage Of Floral Budscontrasting
confidence: 52%
“…Aigeiros, production of 2n pollen was lower than the two hybrids mentioned above (55.67%) (Zhang, 2006). Hybrids, some of which can produce natural 2n pollen, were chosen in many studies and had favorable performance in artificial induction probably because of their unstable genomes that may be doubled more easily (Kang, 2002;Zhang and Kang et al, 2010;Tian et al, 2015). Research on original species in Populus is still at an early stage, and the cytological mechanisms of unreduced gametes formation are not clear.…”
Section: Colchicine Injectionmentioning
confidence: 99%
“…italica , abnormal meiotic phenomena such as multinuclei, multinucleoli, monads, dyads, and polyads have been observed [ 49 ]. Previous studies on diploid Populus hybrids also showed that hybridization tends to induce occurrence of meiotic abnormalities [ 45 , 50 ]. However, compared with the diploid species and hybrids of Populus , although meiosis in ‘Yinzhong’ showed similar abnormalities, the frequency of abnormalities was high in ‘Yinzhong’, suggesting that more abnormalities might be induced by its distant genomic composition and polyploidization.…”
Section: Discussionmentioning
confidence: 99%
“…Production of unreduced gametes has been reported in many species and hybrids of the genus Populus [ 44 , 45 , 50 54 ]. There are multiple cytological mechanisms of unreduced gamete formation, which have been reviewed frequently [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…2). Maich et al (1999) and Tian et al (2015) verified in wheat that there is not always a significant relationship between a high meiotic index value and high fertility. This contradiction could be explained by some mechanisms that act in the final phases of meiosis, meaning that univalents and laggards are inserted in the nuclei of tetrads instead of forming micronuclei, thus increasing the frequency of quartets of tetrads with normal nuclei (Gaur et al 1983).…”
Section: Pollen Viabilitymentioning
confidence: 99%